Working while learning: International students’ rights, realities, and challenges in Australian higher education - Yee Wai Min , Eunice; McKay, Fiona; McKenzie, Hayley; Lippi, Kehla (Journal of International Students, 2026)
Many international students engage in paid employment while studying. This research explores the employment experiences, working conditions, and understandings of the workplace rights of international students in Australia. Semistructured interviews were conducted with ten international students aged over 18 years who were enrolled in an Australian higher education institution. The data were analyzed using reflexive thematic analysis. Three themes were identified: navigating employment; awareness, knowledge, and ability to act on workplace rights; and financial challenges. Participants typically worked because of financial necessity and often had limited awareness of their workplace rights. Many were reluctant to report unfair treatment because they feared job loss or visa consequences and experienced cultural norms that discouraged them from speaking out. The findings suggest that some employers might be hesitant to hire international students, influenced by visa restrictions and cultural perceptions. The study highlights the need for employers, universities, and policymakers to be better supported in asserting their workplace rights and accessing fair employment opportunities.